A potential mechanism for amino acid-controlled crystal growth of hydroxyapatite. Issue 47 (9th November 2015) - Wang, Ziqiu; Xu, Zhijun; Zhao, Weilong; Sahai, Nita
Abstract : Hydroxyapatite morphology regulation via preferential adsorption of amino acids. Abstract : The mineral component of bone, dentin and calcified parts of avian tendon, hydroxyapatite (HAP), has non-stoichiometric composition (idealized as Ca10 (PO4 )6 (OH)2 ), plate-like morphology and nanometer size. This unique crystal morphology contributes to the physico-chemical and biochemical properties of bone. Thus, understanding the mechanism for the controlled growth of plate-like HAP nanocrystals is significant in the study of bone biomineralization. Previous studies have shown that acidic non-collagenous proteins (ANCPs), which are enriched in the residues of acidic amino acids, may play an important role in HAP crystal growth modulation. In this study, glutamic acid (Glu) and phosphoserine (Ser-OPO3 ) were used as model compounds to modify the synthesis of HAP nanocrystals. To identify the mechanisms of amino acids as regulators, X-ray diffraction (XRD), transmission electron microscopy (TEM) and solid state nuclear magnetic resonance (ssNMR) were used. The crystals obtained in the inorganic controls were needle-like, while crystals synthesized in the presence of the amino acids presented a plate-like morphology. The plate-like crystals had a preferred crystal orientation on (300) face, which was lacking in the inorganically grown crystals, indicating preferential adsorption and suppression of growth in specific crystal directions. Ser-OPO3 was more efficient than Glu in modulating HAP nucleation and crystal growth. Furthermore, NMR revealed interactions between the charged side chain groups in amino acids and the crystal surfaces. These results were successfully explained through our MD simulations for the free energy calculation of amino acid binding on HAP crystal faces. The present study revealed that amino acids may act as effective regulators of HAP morphology without the need to invoke large NCPs in bone biomineralization and in designing bioinspired materials for orthopaedic and dental applications.